2022
DOI: 10.1097/md.0000000000031995
|View full text |Cite
|
Sign up to set email alerts
|

A case of EBV encephalomyelitis with positive anti-GFAP-IgG antibody with recurrent fever and dysuresia as the main symptoms: Case report and retrospective analysis

Abstract: Rationale: Due to neuronal destruction caused by Epstein-Barr virus (EBV) infection, exposure to neuronal surface antigens may lead to an imbalance in immune tolerance, which in turn triggers an autoimmune response. In addition, due to the involvement of nonspecific B-cell activation or molecular mimicry, EBV and Glial Fibrillary Acidic Protein (GFAP) receptors may have common epitopes. Viral infection triggers activation of B-cell and cross-reaction with viral antibodies, resulting in autoimmune encephalomyel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 21 publications
(19 reference statements)
0
2
0
Order By: Relevance
“…However, GFAP‐IgG in CSF was detected after 1 month later (titer, 1:10) accompanied by more periventricular lesions. It was also reported that a rare case of EBV encephalomyelitis with negative GFAP‐IgG at onset turned positive GFAP‐IgG after 15 days 7 . The temporal sequence of EBV infection and GFAP‐IgG appearing indicated a causal mechanism.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…However, GFAP‐IgG in CSF was detected after 1 month later (titer, 1:10) accompanied by more periventricular lesions. It was also reported that a rare case of EBV encephalomyelitis with negative GFAP‐IgG at onset turned positive GFAP‐IgG after 15 days 7 . The temporal sequence of EBV infection and GFAP‐IgG appearing indicated a causal mechanism.…”
Section: Discussionmentioning
confidence: 92%
“…It was also reported that a rare case of EBV encephalomyelitis with negative GFAP-IgG at onset turned positive GFAP-IgG after 15 days. 7 The temporal sequence of EBV infection and GFAP-IgG appearing indicated a causal mechanism. It was reported that autoimmune GFAP astrocytopathy could coexist with other antibodies, such as NMDAR-IgG and AQP4-IgG.…”
Section: Discussionmentioning
confidence: 99%